Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Problem with Parity for photons

  1. Oct 18, 2012 #1
    I am trying to understand how it can be shown that under parity transformation we have to have [itex] \hat{P} \hat{a}_{\mathbf{p},\lambda} \hat{P} = - \hat{a}_{-\mathbf{p},\lambda} [/itex], I mean the negative sign (negative intrinsic parity of photon). So I am trying to prove that from the vector nature of four potential it follows that [itex]\eta = -1[/itex] in the relation [itex] \hat{P} \hat{a}_{\mathbf{p},\lambda} \hat{P} = \eta \hat{a}_{-\mathbf{p},\lambda} [/itex]

    In radiation gauge the second quantized four-potential is:
    \mathbf{A}(x) = \int \frac{d^3p}{(2 \pi)^3 \sqrt{2 \omega_p}} \sum_{\lambda =1,2} \left [ \boldsymbol{\epsilon}(\mathbf{p}, \lambda) \hat{a}_{\mathbf{p},\lambda} e^{-ipx} +\boldsymbol{\epsilon}^*(\mathbf{p}, \lambda) \hat{a}_{\mathbf{p},\lambda}^* e^{ipx} \right ]
    From vector nature of $\mathbf{A}$ we should have:
    \hat{P} \mathbf{A}(t,\mathbf{x}) \hat{P} = - \mathbf{A}(t,\mathbf{x'}=-\mathbf{x})

    Applying parity operator:
    \hat{P} \mathbf{A} \hat{P}= \int \frac{d^3p}{(2 \pi)^3 \sqrt{2 \omega_p}} \eta \sum_{\lambda =1,2} \left [ \boldsymbol{\epsilon}(\mathbf{p}, \lambda) \hat{a}_{-\mathbf{p},\lambda} e^{-ipx} +\boldsymbol{\epsilon}^*(\mathbf{p}, \lambda) \hat{a}_{-\mathbf{p},\lambda}^* e^{ipx} \right ] \\
    \hat{P} \mathbf{A}(x) \hat{P}= \int \frac{d^3p'}{(2 \pi)^3 \sqrt{2 \omega_p}} \eta \sum_{\lambda =1,2} \left [ \boldsymbol{\epsilon}(-\mathbf{p'}, \lambda) \hat{a}_{\mathbf{p'},\lambda} e^{-ip'x'} +\boldsymbol{\epsilon}^*(\mathbf{-p'}, \lambda) \hat{a}_{\mathbf{p'},\lambda}^* e^{ip'x'} \right ]

    On the other hand for circular polarization vectors the flipping of the momentum sign ammouts to rotation of the direction of momentum by 180, e.g. around the axes $x$:
    \boldsymbol{\epsilon}(\mathbf{p},1) = \frac{1}{\sqrt{2}}\{1,i,0\} \Rightarrow \boldsymbol{\epsilon}(-\mathbf{p},1) = \frac{1}{\sqrt{2}}\{1,-i,0\} \\
    \boldsymbol{\epsilon}(\mathbf{p},2) = \frac{1}{\sqrt{2}}\{1,-i,0\} \Rightarrow \boldsymbol{\epsilon}(-\mathbf{p},2) = \frac{1}{\sqrt{2}}\{1,i,0\}

    We see that polarizations exchange their places in the equation. Under spatial inversion all coordinates would be reversed and a minus sign would appear in the equation (4). Hence

    \hat{P} \mathbf{A}(x) \hat{P}= \int \frac{d^3p'}{(2 \pi)^3 \sqrt{2 \omega_p}} (-\eta) \sum_{\lambda =1,2} \left [ \boldsymbol{\epsilon}(\mathbf{p'}, \mp) \hat{a}_{\mathbf{p'},\pm} e^{-ip'x'} +\boldsymbol{\epsilon}^*(\mathbf{-p'}, \mp) \hat{a}_{\mathbf{p'},\pm}^* e^{ip'x'} \right ]

    I don't understand how can this equation (7) be compared with equation (2) to deduce that [itex]\eta=-1[/itex], the polarizations echanged their places!!!!
  2. jcsd
  3. Oct 18, 2012 #2


    User Avatar
    Science Advisor

    Remember that, although momentum is a normal (polar) vector, spin is an axial vector. So that under a parity operation, p → -p but ss. The components of the polarization vectors remain unchanged: ε(-p,1) is still (1/√2){1, i, 0}.
  4. Oct 18, 2012 #3
    That I intuitively realize but I need mathematically sound proof. Which part of my logic fails mathematically?
    Last edited: Oct 18, 2012
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook